Insights into the molecular mechanisms underlying the function of lysyl oxidase like 1 in cancers - Xinmeng Wang; Xiaoyi Wang; Yihan Li; Dan Zhao; Jintao He; Lin Wang; Zhengliang Li; Wei Xiong (PeerJ)
Cancer is one of the primary causes of human mortality and a significant barrier to increasing human life expectancy. The effective screening, early diagnosis, and treatment of cancer have long been clinical challenges, and thus new biomarkers or molecular targets must be identified to improve the diagnosis and treatment of cancer patients. Lysyl oxidase like 1 (LOXL1), a secreted copper-dependent amine oxidase, is commonly expressed in a variety of cell types. LOXL1 can maintain the steady state of elastin, engage in extracellular matrix (ECM) remodelling. LOXL1 has diverse biological functions, and its dysregulation is the basis of many clinical diseases. The abnormal expression or activation of LOXL1 can disrupt the cellular microenvironment, contributing to the development of various diseases, such as atherosclerosis, tissue damage, fibrosis, and cancer. Recent research has revealed that LOXL1 is often overexpressed in a majority of cancers, where it plays a role in regulating tumor growth and metastasis. However, some studies have also suggested that LOXL1 may have a tumor-suppressive function. Research has indicated that the LOXL1 protein is reduced in human renal cell carcinoma (RCC) and bladder cancer (BLCA), where it acts to suppress tumor growth. Conversely, it is upregulated in human salivary adenoid cystic carcinoma (SACC), non-small cell lung cancer (NSCLC), pleural mesothelioma (PM), brain glioma, prostate cancer (PRAD), gastric cancer (GC), breast cancer (BC), thyroid carcinoma (THCA), pancreatic adenocarcinoma (PAAD), and osteosarcoma (OS). The expression of LOXL1 in colorectal cancer (CRC) remains a topic of debate, as it may either be upregulated or downregulated. These findings imply that LOXL1 may have a dual role in cancer, either inhibiting or facilitating carcinogenesis. This article provides a comprehensive review of the structure and function of LOXL1, along with its associations with cancer. Additionally, it explores the role of LOXL1 in tumor microenvironment remodeling, tumorigenesis, metastasis, and the molecular mechanisms that underpin these processes.